Partial Thickness Sclerectomy for Uveal Effusion Syndrome in nanophthalmic eyes - Simanta Khadka; Raghundandan Byanju; Sangita Pradhan; Saurav Piya; Sweta Singh; Ritesh Shah; Santosh Chaudhary (International Journal of Retina, 2021)
Introduction: Nanophthalmos characterized by short axial length, high lens-to-eye ratio and thick sclera, is more prone to develop uveal effusion syndrome (UES). This rare entity can result in idiopathic exudative detachment of the choroid, ciliary body and retina. Abnormality in the scleral thickness with resultant obstruction of the vortex veins and reduced trans-scleral drainage of fluid is responsible for exudative retinal detachment (ERD). Methods: A retrospective study of UES in nanophthalmic patients treated with partial thickness sclerectomy in tertiary eye care centre from January 2015 to June 2019. Five eyes of five patients (four males and one female) with a diagnosis of nanophthalmos suffered from angle closure glaucoma associated with ERD. Raised intra-ocular pressure (IOP) not amenable to conservative medical management were subjected to surgery. Lamellar sclerectomy was performed in two or more quadrants without drainage which was judged on the basis of maximum amount of exudative fluid present in the subsequent quadrants. Results: The average age at surgery was 39.2 years and the mean follow-up duration was 9.2 months (6 to 18 months). Revision sclerectomy was required in 2/5 (60%) eyes. The serous fluid gradually resolved and retina remained reattached at the end of final follow up. The useful vision was preserved and IOP was normalized. Conclusion: Nanophthalmic UES remains a challenging clinical entity. Partial thickness sclerectomy may be an effective option in the treatment of nanophthalmic UES, not amenable to the conventional medical management in a low resource setup.